Allamanda cathartica flower's aqueous extract-mediated green synthesis of silver nanoparticles with excellent antioxidant and antibacterial potential for biomedical application. (13th January 2016) - Karunakaran, Gopalu; Jagathambal, Matheswaran; Gusev, Alexander; Kolesnikov, Evgeny; Mandal, Arup Ratan; Kuznetsov, Denis
Abstract: Abstract : The present study aimed to develop an easy method to synthesis silver nanoparticles (AgNPs) using Allamanda cathartica flower extracts. The phytocompounds converted silver nitrate into AgNPs. UV–visible spectra show the maximum absorbance between 350 and 450 nm and x-ray powder diffraction results reveal AgNPs crystallized in cubic phase. Fourier transform infrared spectrum reveals that phytochemicals act as a reducing, stabilizing, and capping agent. Energy-dispersive spectrum, particle size distribution, and transmission electron microscopy analyses show that the nanoparticles are pure, spherical shaped with size of 39 nm. In addition, AgNPs show significantly antibacterial and antioxidant activity compared with commercial antibiotic. Hence, A. cathartica flower extracts mediated AgNPs which will be a new candidate for biomedical applications.